Effect of turbulent motions at different length scales on turbulent premixed swirl-stabilised flame topology. (13th August 2019) - Minamoto, Yuki; Tanahashi, Mamoru
Abstract: Three-dimensional direct numerical simulation data of H2 -air turbulent swirling premixed combustion at two different swirl numbers are analysed to investigate the local reaction zone morphology and its relation with local turbulent motions at different length scales. The effect of small scale turbulent mixing on local flames is investigated, and the results have shown that the contribution of microscale turbulent diffusivity on the local flamelet is insignificant, although there is some evidence of flame thinning for the higher swirl number case. The flame morphology such as high-level convolution and interacting flames, on the other hand, shows greater influence on local flamelets, suggesting the importance of local reaction zone topology on overall combustion processes. The local reaction zones are analysed by using the shapefinders to quantify their topology. Although the shapefinders showed various local reaction zone shapes consisting of "pancakes" and "tubes" and intermissive intense reaction zone distributions, the smallest characteristic length scale shows that the local reaction zones are thin. Finally, the relationship between these local reaction zone topology and turbulent motions at different sizes were discussed. The local reaction zone topology has a direct relation with Taylor microscale, integral length scale and their associated velocity scale, whereas almost no correlation is observed with Kolmogorov length scale, in the presence of inhomogeneous turbulence and strong mean shears. The present results suggest the importance of Taylor microscale on flame surface topology, which is often understated in turbulent combustion modelling frameworks. Highlights: Direct numerical simulation of turbulent swirling premixed combustion were employed. Local flame topology and its relation with local turbulence were investigated. A mathematical tool to quantify local flame shape was applied for the analysis. Local flame topology leads to large scale events to modify local flame structure. Turbulence scales important for flame topology were clarified.